Asymmetric total syntheses of (+)-2, 5-dideoxy-2, 5-imino-d-glucitol [(+)-DGDP] and (−)-1-deoxymannojirimycin [(−)-DMJ] via an extended chiral 1, 3-oxazine. Issue 25 (20th June 2018) - Myeong, In-Soo; Jung, Changyoung; Kim, Ji-Yeon; Park, Seok-Hwi; Ham, Won-Hun
Graphical abstract: Highlights: Reporting a total synthesis of (+)-DGDP, a polyhydroxylated pyrrolidine. Reporting a total synthesis of (−)-DMJ, a polyhydroxylated piperidine. Highly stereoselective dihydroxylation was accomplished by Osmium tetroxide. A novel chiral synthon anti, syn, anti -oxazine was used for the total syntheses. Abstract: The asymmetric total syntheses of (+)-2, 5-dideoxy-2, 5-imino-d -glucitol [(+)-DGDP] 1 and (−)-1-deoxymannojirimycin [(−)-DMJ] 2 were achieved using an extended chiral 1, 3-oxazine. The key synthetic strategies included extension of the chirality of anti, syn -oxazine 3 using diastereoselective dihydroxylation, and piperidine and pyrrolidine ring formation. Starting from readily available anti, syn -oxazine 3, (+)-DGDP 1 was synthesized in 5 steps with 31.6% overall yield and (−)-DMJ 2 was synthesized in 4 steps with 60.6% overall yield.